2007
DOI: 10.1016/j.cryobiol.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The temperature of intracellular ice formation in mouse oocytes vs. the unfrozen fraction at that temperature

Abstract: We have previously reported [Cryobiology 51 (2005) 29-53] that intracellular ice formation (IIF) in mouse oocytes suspended in various concentrations of glycerol and ethylene glycol (EG) occurs at temperatures where the percentage of unfrozen water is about 6% and 12%, respectively, even though the IIF temperatures varied from -14 to -41 degrees C. However, because of the way the solutions were prepared, the concentrations of salt and glycerol or EG in that unfrozen fraction at IIF were also rather tightly gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Some of the 1X data in the Mouse Oocytes-Variable R section also appear in the Constant R section. All the data in the Constant R section come from Table 4 of [4]; however, some of the values for U, m s , and m CPA , here differ slightly from those in [4]. This is because, here, the means were calculated by Eq 1 in the footnote of Table 1, whereas in [4], they were calculated by Eq 2.…”
Section: Tablementioning
confidence: 77%
See 3 more Smart Citations
“…Some of the 1X data in the Mouse Oocytes-Variable R section also appear in the Constant R section. All the data in the Constant R section come from Table 4 of [4]; however, some of the values for U, m s , and m CPA , here differ slightly from those in [4]. This is because, here, the means were calculated by Eq 1 in the footnote of Table 1, whereas in [4], they were calculated by Eq 2.…”
Section: Tablementioning
confidence: 77%
“…As a consequence, the weight ratios of CPA to salt (R values) varied in each solution, and different isopleths of the ternary phase diagram were applicable. The middle third of Table 4 summarizes the data in [4]. In that case, the external solutions were prepared to hold the R value constant in each set.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…One indication of normality is their morphological appearance. A second is that they shrink or swell in anisosmotic solutions of glycerol/PBS or EG/PBS in quantitative accord with that calculated from fundamental osmotic equations (For example, see Table 7 of Mazur et al [14]. Thirdly, M. Kasai (personal communication) has found that 84% of ICR oocytes vitrified in the same medium and by the same procedure developed to the 2-cell stage after dezonation and in vitro fertilization, a percentage nearly equal to the 89% for untreated controls.…”
Section: Source Of Oocytesmentioning
confidence: 86%